Satisfaction of using hearing protection devices among industrial workers - Yahya, Siti Najihah; A. Rahman, Nor Azlina; Razali, Ailin; A Rahman, Nor Iza (Association of Indian pharmacist-AIP, 2016)
TheprevalenceoNfoise-InducedHearingLosisincreasingwodrlwide.Majorfactorscontributetothisituationis the breach of the preventive measures. Thstisudy aimed to identify factors that caused the industrial workers to ignore the usage of thehearing protection device(HPD). Sem-istructured focus group disucssion was conducted to the sawmill workers of Pahang, Malay.siPaurposive sampling method was performed to obtpaainrticipants,who was exposed to continuous noise, working tinhe industrial fieldand frequently or never used the HPD during working. Participants werediffered in term of gender, age, working experience and job. The condufcotceuds group discussion was recorded and all related information was transcribed. Analysis of the theme for the study was conducted using QSR Nvivo 9.2. Three mnaithemes were identified which are: uncomfortable, less awareness and barrier in communication. 58% of the workers reported on uncomfortable feeling wh2il%e 4were lack of awareness and 25% feel that the devices createad barrier in communication. Therefore, asncuomfortable feeling was the main cauosfe the industrial workers not to wear the HPD, new types of HPD that follows user requirement should be invented.